Environmental Management Accounting, Carbon Disclosure Emission, and Their Effects on Environmental Performance with Green Competitive Advantage as a Moderating Variable - Ismawati HARIBOWO; Yvonne AUGUSTIN (PT Keberlanjutan Strategis Indonesia, 2024)
This study aims to determine whether Environmental Management Accounting, Carbon Emission Disclosure affects the Environmental Performance by using Green Competitive Advantage as a moderating variable. Respondents in this study were 45 respondents. Analysis Method using Moderate Regression Analysis. The results showed that Environmental Management Accounting had no effect on Environmental Performance. Carbon Emission Disclousure affects Environmental Performance. Green Competitive Advantage has not been proven to moderate the influence of Environmental Management Accounting on Environmental Performance. Green Competitive Advantage has not been proven to moderate the effect of Carbon Emission Disclosure on environmental performance.